(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The long lastingcrisis on the Polish countrysideand agriculture enforces a particu-lar need for corrective action. Revival of rural areas may be effected mainly by changes in non-agricultural sphere and at the same time may create new jobs in many fieldsof agriculture. The condition of improvement is to release the activity of municipal com-munityin order to find possible advantagesof the existing reserves. In the rural areas there are many ideas, programs, projectssupporting economic growth on the local level. The article contains an overview of the theoretical concepts that can serve the institu-tions andlocal communities to preparetheir own vision of socio-economic development of the administrative units.